2020
DOI: 10.12688/hrbopenres.12980.2
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and enablers to Caregivers Responsive feeding Behaviour (CRiB): A mixed method systematic review protocol

Abstract: Background: Childhood overweight and obesity is a major public health issue. Responsive feeding has been identified as having a protective effect against child overweight and obesity, and is associated with healthy weight gain during infancy. Responsive feeding occurs when the caregiver recognises and responds in a timely and developmentally appropriate manner to infant hunger and satiety cues. Despite its benefits, responsive feeding is not ubiquitous. To better support caregivers to engage in responsive feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The review is reported in line with the Preferred Reporting Items for Systematic Review and Meta‐Analysis (PRISMA‐P) guidelines (see Supporting Information S1). The protocol has been published 19 and registered in PROSPERO (CRD42019144570).…”
Section: Methodsmentioning
confidence: 99%
“…The review is reported in line with the Preferred Reporting Items for Systematic Review and Meta‐Analysis (PRISMA‐P) guidelines (see Supporting Information S1). The protocol has been published 19 and registered in PROSPERO (CRD42019144570).…”
Section: Methodsmentioning
confidence: 99%